Teacher and parent perspectives on extracurricular activities for students with intellectual and developmental disabilities - Cain, Irina; Bruno, Lauren; Agran, M.; Wojcik, Andrew; Achola, Edwin; Thoma, Colleen; Nixon, Cynthia; Tamura, Ronald (Inclusion, 2025)
Keywords: Extracurricular activity; Intellectual disability; Qualitative research; Semi-structured interview; dept.sed

Participation of students with intellectual and developmental disabilities in extracurricular activities: does inclusion end at 3:00? - Agran, Martin; Achola, Edwin; Nixon, Cynthia Allen; Wojcik, Andrew; Cain, Irma; Thoma, Colleen; Austin, Kira M.; Tamura, Ronald B. (Education and Training in Autism and Developmental Disabilities, 2017)
Although participation in extracurricular activities for students with intellectual and developmental disabilities has been advocated, a limited number of students appear to be involved in such activities. Further, there is little empirical research on how extracurricular activities are valued, supported, and encouraged. This study surveyed a sample of special educators across five states to learn about their opinions regarding extracurricular activities. As reported in other research, the findings confirm that few students participated in these activities; few parents requested these services for their children; and few teachers believed that planning them is their responsibility, despite the fact that they thought these activities were of value and provided several benefits. The implications of these findings are discussed.
Keywords: dept.sed